Green Human Resource Management Practices on the Sustainable Performance of India's Sports Sector - Sahilali Saiyed; Mahedi Hasan; Raiyan Chowdhury; Md Akmal Hossain; Sale Musa; Vimal Kumar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: As sustainability becomes a major global concern, the sports sector also plays a significant role in environmental degradation. This makes it a crucial area of focus for research aimed at achieving sustainability goals.